Coronary angiography finding of exercise tread mill test positive patients in a tertiary care center - Shrestha, Amit; Thapa, Sanjeev; Shakya, Shilendra; Shahi, Ravi (Journal of Chitwan Medical College, 2017)
Background: The diagnosis rate of coronary artery disease (CAD) has been dramatically increased with the development of interventional technique. Coronary angiography (CAG) is the “gold standard” tool for CAD diagnosis. Due to its invasive property, CAG has been limited. Treadmill test (TMT) is still broadly used as an economic and simple method to screen and assist the diagnosis of CAD. However, correct interpretation of such data is essential in determining diagnostic and treatment strategies. Methods: All the patients attending outpatient department of Manmohan Cardiothoracic Vascular and Transplant Center (MCVTC) and having positive findings in tread mill stress test (TMT) using Bruce protocol underwent selective coronary angiography (CAG), in MCVTC Cath Lab using standard technique and were analyzed in multiple views with significant coronary stenosis defined as of ≥70 % lesion, 50-60% as borderline and 20-30% as minor coronary artery disease. Results: A total of 303 patients (mean age 52.8 ±9.7 yrs) were included during a study period of approximately 1½ yrs (Oct 2015 to Dec 2016), among whom male were of average 53.6 ±10.5 yrs and female were of 51.7±8.6 yrs. Risk factor estimation among patients showed that 49.3 % were hypertensive, 29.9% were overweight, 15.2% were diabetic and 5.7% were smoker. Coronary angiography of patients revealed normal coronaries in 114(54.0%), borderline lesion in 29(13.7%) and significant lesion in 68 (32.2%). Among those with diagnosed coronary artery disease (CAD), 48(22.7%) had single vessel disease, 29(13.7%) had double vessel disease and 14(6.6%) had triple vessel disease. The sub group analysis based on of risk factor and coronary artery disease showed coronary artery diseases was highest among diabetics (57.7%) followed by smokers (55%) compared. The risk of Coronary artery disease found to be significantly higher among patient with ≥2 CAD risk factor. Males with stress test positive had significantly higher chances of having CAD than females (53% vs 35% respectively). Conclusion: Coronary artery disease (CAD) among patients with TMT positive status is higher in patients with diabetics and smokers, especially those with two or more CAD risk factors. Results of this study showed that the pretest probability of treadmill stress-test is higher in males with two or more CAD risk factor especially diabetes and smoking compared to the female counterparts with similar factors, so should be supplemented by other non-invasive techniques (such as stress echocardiography, myocardial perfusion imaging) for further confirmation of diagnosis. (such as Astress echocardiography, myocardial perfusion imaging) for further confirmation of diagnosis.